2018
DOI: 10.3390/s18041129
|View full text |Cite
|
Sign up to set email alerts
|

Non-Mutually Exclusive Deep Neural Network Classifier for Combined Modes of Bearing Fault Diagnosis

Abstract: The simultaneous occurrence of various types of defects in bearings makes their diagnosis more challenging owing to the resultant complexity of the constituent parts of the acoustic emission (AE) signals. To address this issue, a new approach is proposed in this paper for the detection of multiple combined faults in bearings. The proposed methodology uses a deep neural network (DNN) architecture to effectively diagnose the combined defects. The DNN structure is based on the stacked denoising autoencoder non-mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 27 publications
0
11
0
Order By: Relevance
“…Specifically, when using popular feature extraction methods that analyze features from the time domain, frequency domain, or time-frequency domain, it is very difficult to identify the fault characteristics under variable working conditions [ 15 , 16 , 17 , 18 , 19 , 20 ]. Therefore, research on new and effective methods for the condition monitoring of rolling element bearings has become a challenging and valuable task [ 21 , 22 , 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, when using popular feature extraction methods that analyze features from the time domain, frequency domain, or time-frequency domain, it is very difficult to identify the fault characteristics under variable working conditions [ 15 , 16 , 17 , 18 , 19 , 20 ]. Therefore, research on new and effective methods for the condition monitoring of rolling element bearings has become a challenging and valuable task [ 21 , 22 , 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…These fault diagnosis studies have shown that diagnosis of bearing wear can reduce maintenance expenses and enhance machine reliability [6,[12][13][14][15][16]. Bearing fault diagnosis studies have extensively investigated vibration signals and motor current analysis [17,18]. Multiple signature analysis of vibrations and motor currents has also been researched to improve reliability [19].…”
Section: Introductionmentioning
confidence: 99%
“…Primarily, bearing faults occur due to localized imperfections, i.e., cracks or spalls. These flaws create shocks and stimulate high-occurrence reverberations of the bearings and machine assembly due to the recurring effect on spinning parts [17]. Time-frequency signal analysis approaches have been employed to solve these issues, such as fast Fourier transform (FFT) and short-term-Fourier transform (STFT), which convert time-domain signals into frequency-domain signals for further analysis [20].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Generally, this involves condition monitoring using appropriate sensors, assessment of the current health status of the machines and predicting their future health by analyzing acquired measurement data, and utilization of this knowledge to improve the overall reliability and availability of the machines [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 ]. Rolling element bearings are among the most significant contributors to the failure of critical industrial equipment, such as induction motors [ 10 , 11 ]. Consequently, they have received considerable research attention [ 2 , 3 , 4 , 5 , 7 , 8 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%